Pengaruh Kinerja Pegawai Terhadap Pemanfaatan Teknologi Informasi Laporan Keuangan Pada Bidang Teknologi Informasi Dan Komunikasi Polda Bengkulu - Sarfah, Erma; Gustini, Gustini; Hartono, Rudi (STIA Bengkulu, 2025)
The purpose of this study is to determine the performance of employees in the field of information technology and communication of the Bengkulu Police. To determine the utilization of financial reporting information technology in the field of information technology and communication of the Bengkulu Police. To determine the effect of employee performance on the utilization of financial reporting information technology in the field of information technology and communication of the Bengkulu Police. Sampling in this study used the Total Sampling technique. Data collection methods by conducting observations, questionnaires, documentation and literature studies. Data analysis techniques with Descriptive Tests, data quality tests, Classical assumption tests, and Hypothesis tests. The results of the study showed that the assessment results showed that employee performance in the field of Information Technology and Communication of the Bengkulu Police was included in the very good category. The results of this assessment indicate that the utilization of Financial Report Information Technology in the Field of Information Technology and Communication of the Bengkulu Police is included in the very good category. The results of the study obtained a significance value of 0.000 <0.05, which states that Employee Performance has an influence on the Utilization of Financial Report Information Technology in the Field of Information Technology and Communication of the Bengkulu Police..